ANALYSIS OF DIFFERENCES IN HYDROCARBON ACCUMULATION IN SHALLOW ZONE AT TUNU FIELD, KUTAI BASIN, EAST KALIMANTAN - Setiawan, Thomas
Tunu field is the largest gas field at Mahakam, East Kalimantan, which is operated by international company, Total E&P Indonesie, in collaboration with Japanese company INPEX in Production Sharing Contract (PSC). Tunu field was discovered in 1977 and began to produce in 1990. Until now more than 9 Tcf of gas has been produced from more than 1000 wells. The majority of the production comes from the Tunu Main Zone Layer (TMZ) at depth 2200 – 3500 mSS.